2008
DOI: 10.1124/jpet.108.140350
|View full text |Cite
|
Sign up to set email alerts
|

Centrally Active Allosteric Potentiators of the M4 Muscarinic Acetylcholine Receptor Reverse Amphetamine-Induced Hyperlocomotor Activity in Rats

Abstract: Previous clinical and animal studies suggest that selective activators of M 1 and/or M 4 muscarinic acetylcholine receptors (mAChRs) have potential as novel therapeutic agents for treatment of schizophrenia and Alzheimer's disease. However, highly selective centrally penetrant activators of either M 1 or M 4 have not been available, making it impossible to determine the in vivo effects of selective activation of these receptors. We previously identified VU10010 [3-amino-N-(4-chlorobenzyl)-4, 6-dimethylthieno[2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
209
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(223 citation statements)
references
References 29 publications
13
209
1
Order By: Relevance
“…Previous efforts to develop highly selective orthosteric agonists of the individual muscarinic subtypes have not been successful. However, selective positive allosteric modulators of the M 4 mAChR have been developed recently (Brady et al, 2008;Chan et al, 2008), and in preclinical studies, positive allosteric modulation of M 4 mAChR has been shown to attenuate apomorphine-induced deficits in prepulse inhibition (Chan et al, 2008) and amphetamineinduced hyperactivity in rats (Brady et al, 2008), supporting the potential role of the M 4 mAChR as a future target for treatment of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to develop highly selective orthosteric agonists of the individual muscarinic subtypes have not been successful. However, selective positive allosteric modulators of the M 4 mAChR have been developed recently (Brady et al, 2008;Chan et al, 2008), and in preclinical studies, positive allosteric modulation of M 4 mAChR has been shown to attenuate apomorphine-induced deficits in prepulse inhibition (Chan et al, 2008) and amphetamineinduced hyperactivity in rats (Brady et al, 2008), supporting the potential role of the M 4 mAChR as a future target for treatment of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…These agents provide new opportunities to determine the physiological roles of individual mAChRs in the basal ganglia circuitry and to assess the antiparkinsonian efficacy of highly selective mAChR antagonists (Conn et al, 2009a, b), but to do so the full specificity profile of these compounds must be characterized in vivo. In this regard, recent in vivo studies indicate that the allosteric modulators display favorable pharmacokinetic properties and bloodbrain barrier permeability, and have confirmed their potential therapeutic benefits in rodent models of Alzheimer's disease and schizophrenia (Caccamo et al, 2006;May et al, 2007;Brady et al, 2008;Chan et al, 2008;Shekhar et al, 2008;Conn et al, 2009a, b;Bridges et al, 2010;Digby et al, 2010 A 2A receptor antagonists (Schwarzschild et al, 2006;Menon and Stacy, 2008;Morelli et al, 2010;Shah and Hodgson, 2010). Adenosine is a ubiquitous purine with signaling properties that mediate its effects through four subtypes of G-protein-coupled adenosine receptors: A 1 , A 2A , A 2B , and A 3 (Schwarzschild et al, 2006;Menon and Stacy, 2008;Morelli et al, 2007Morelli et al, , 2009Morelli et al, , 2010Shah and Hodgson, 2010).…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 99%
“…injection of GA, the animals were sacrificed, and kidneys, colons, and tumors were collected and stored at -80°C. Tissue levels of CS, 11-keto-corticosterone, GA, and GE were measured using high-performance liquid chromatography coupled with electrospray tandem mass spectrometry (53). GA and GE were from Sigma-Aldrich, CS was from ICN Biomedicals, and 11-keto-corticosterone was from Steroids.…”
Section: Methodsmentioning
confidence: 99%